EncyCloudPrado: didactic possibilities of new technologies for accessing information in museums - Carolina Fernández Castrillo; Bernd Lintermann (Centro de Estudios Financieros, 2017)
The role and the development of museums in the contemporary world is closely related to the possibilities offered by the information and communication technologies (ICT). In line with the educational vocation of museums as cultural institutions, this paper offers a didactic resource to provide an easier access to information and the visualization of the cultural background in the digital age. In the framework of this research it was created the prototype EncyCloudPrado (2016), an interactive installation that allows searches through the online Museo Nacional del Prado's encyclopedia. The results are projected on a 360-degree widescreen as dynamic collages of sounds, documents and images, turning web browsing into a spatial experience. The aim of this study is to determine the degree of acceptance of the use of interactive installations in immersive environments by the generation Z as possible learning tools. It will also be assessed if this type of initiatives may be an incentive to attract more visits to museums and to promote the access to their funds.